Development and validation of the 23-item preterm birth risk assessment scale-Korean version - Jeung-Im Kim (BMC, 2023)
Abstract Background Preterm birth (PTB) is a complex and significant challenge in obstetrics. Thus, clinicians and researchers have paid a keen interest in the identification of women at a high risk for PTB. This study aimed to develop a PTB risk assessment scale based on the preliminary 32-item Preterm Birth Risk Assessment Scale-Korean version (PBRAS-K). Methods We enrolled 298 participants (167 in the exploratory factor analysis group from March 3, 2021 to August 31, 2021 and 131 in the confirmatory factor analysis group from December 3, 2021 to February 14, 2022) who delivered before 37+0 weeks after experiencing preterm symptoms and were admitted to high-risk pregnancy maternal-fetal intensive care units (MFICUs). After an item-reduction process in the exploratory factor analysis, the psychometric property scales were assessed using SPSS Statistics version 27.0, and the confirmatory factor analysis was conducted using AMOS version 27.0. Results The Kaiser-Meyer-Olkin (KMO) test and Bartlett's χ2 test of sphericity confirmed the adequacy of the sample for factor analysis (KMO = .81 (> .80), χ2 = 1841.38, p < .001). The final version of the PBRAS-K comprised 23 items within seven dimensions. Factor analysis identified items explaining 65.9% of the total variance. The PBRAS-K achieved a mean score of 35.58 (± 10.35) and showed high internal consistency and satisfactory reliability (Cronbach's alpha = .85). Regarding concurrent validity, the PBRAS-K exhibited a low-to-moderate correlation with the PTB risk (r = .45, p < .001). As for criterion validity and convergent validity, the PBRAS-K showed a positive and high correlation with the Somatic Awareness Scale with Spontaneous Preterm Labor (SPL-SAS) (r = .65, p < .001) and pregnancy-related stress (r = .57, p < .001), respectively. Risk scoring for preterm delivery and SPL-SAS were moderately correlated (r = .53, p < .001). Conclusions PBRAS-23-K is a valid and reliable instrument for assessing the risk for PTB in pregnant women. Clinical nurses are encouraged to apply and obtain information regarding effective interventions in MFICUs. This scale provides meaningful results and reflects the opinions of women who had experienced PTB. The PBRAS-23-K should be evaluated for standardization and cut-off scores using larger sample sizes in the future.